2022
DOI: 10.1021/acs.inorgchem.2c01534
|View full text |Cite
|
Sign up to set email alerts
|

NiCoPd Inlaid NiCo-Bimetallene for Efficient Electrocatalytic Methanol Oxidation

Abstract: Pd-based metallenes have attracted great attention recently as newly burgeoning two-dimensional (2D) materials, attributed to their significantly increased active surface areas and intrinsic electrocatalytic activities. Therefore, they could be used as a potential candidate as the highperformance electrocatalyst for methanol oxidation reactions (MORs) in the direct methanol fuel cell. Herein, a new strategy is proposed to fabricate NiCoPd inlaid NiCo-bimetallene (NiCoPd/NiCo-bimetallene) by the structure direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Two-dimensional (2D) nanostructures, with a large surface-to-volume ratio, high electron mobility, and sufficient active sites, have attracted more focus in catalytic fields. Metallene, composed of bare metal atoms with atomical thickness, possesses highly curved geometrical configurations, high density of unsaturated metal atoms, and outstanding electronic conductivity, , which has a wide range of applications in electrocatalysis. In order to decrease the adsorption energy of oxygen, the introduction of another metal into the Pd lattice is a promising strategy, which not only effectively modifies the electronic structure of Pd and thus optimizes ORR performance but also decreases the usage of noble metals. It has been reported that the PdCu alloy is considered as a more promising ORR electrocatalyst because of the suitable oxygen adsorption energy . However, the anisotropic 2D ultrathin bimetallic nanostructures possess high surface free energy, which is thermodynamically favorable to aggregation. , Therefore, developing a facile method for the construction of ultrathin 2D alloy nanomaterials for fuel cells is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) nanostructures, with a large surface-to-volume ratio, high electron mobility, and sufficient active sites, have attracted more focus in catalytic fields. Metallene, composed of bare metal atoms with atomical thickness, possesses highly curved geometrical configurations, high density of unsaturated metal atoms, and outstanding electronic conductivity, , which has a wide range of applications in electrocatalysis. In order to decrease the adsorption energy of oxygen, the introduction of another metal into the Pd lattice is a promising strategy, which not only effectively modifies the electronic structure of Pd and thus optimizes ORR performance but also decreases the usage of noble metals. It has been reported that the PdCu alloy is considered as a more promising ORR electrocatalyst because of the suitable oxygen adsorption energy . However, the anisotropic 2D ultrathin bimetallic nanostructures possess high surface free energy, which is thermodynamically favorable to aggregation. , Therefore, developing a facile method for the construction of ultrathin 2D alloy nanomaterials for fuel cells is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…19−21 As a new class of graphene-like 2D metal nanomaterials, metallene not only exposes numerous surface atoms as catalytically active centers but also has an atomically thin thickness. 22,23 For example, Wang's group successfully prepared Pd nanobeltbased materials, which were applied in an efficient electrocatalytic reaction. 24 In addition to modulating the morphological structure, lattice strain engineering and electronic structure modification of catalysts are also essential for enhancing electrocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that modifying the morphological structure of Pd-based catalysts influences their catalytic performance. Among the various structures, the two-dimensional (2D) structure possesses special electronic, photonic, and surface properties that can greatly boost its catalytic activity. As a new class of graphene-like 2D metal nanomaterials, metallene not only exposes numerous surface atoms as catalytically active centers but also has an atomically thin thickness. , For example, Wang’s group successfully prepared Pd nanobelt-based materials, which were applied in an efficient electrocatalytic reaction . In addition to modulating the morphological structure, lattice strain engineering and electronic structure modification of catalysts are also essential for enhancing electrocatalytic properties. Recently, the incorporation of nonmetallic elements to induce the lattice strain and tune the electronic structure of metal has become a universal and powerful strategy. The adsorption behavior of intermediates in electrocatalytic reaction could be optimized by the induced strain effect, thus enhancing catalytic performance. , Meanwhile, it has been reported that tuning the electronic structure of metals through doping may boost its ORR activity and durability. , The intercalation strategy of B-element is one of the effective ways to give rise to lattice expansion and electronic structure modulation of the catalyst. , For instance, Liu and co-authors reported that inserting B atoms into Pd crystals could enlarge Pd–Pd interatomic spacings and contribute to the electronic effect, thereby weakening the adsorption between oxygen-containing intermediates and the Pd surface .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 The durability of electrocatalysts is an important factor in MOR activity, and most of the reported electrocatalysts had very low durability because the CO intermediate generated during methanol oxidation blocked the active sites. 40,41 As a result, there is an urgent need to develop electrocatalysts with high durability for MOR. The majority of the reported NiCo-based electrocatalysts demonstrated complete methanol oxidation to convert methanol into CO 2 , but it is required to selectively convert methanol into a valuable formate product.…”
Section: Introductionmentioning
confidence: 99%